The Two-Stroke Poppet Valve Engine. Part 2: Numerical Investigations Of Intake And Exhaust Flow Behaviour - Muhammad Kamili, Zahidi; Mohd Razali, Hanipah (2017)
A two-stroke poppet valve engine is developed to overcome the common problems in conventional two-stroke engine designs. However, replacing piston control port with poppet valve will resulted different flow behaviour. This paper presents the model and simulation result of three-dimensional (3D) port flow investigation of a two-stroke poppet valve engine. The objective of the investigation is to conduct a numerical investigation on port flow performance of two-stroke poppet valve engine and compare the results obtained from the experimental investigation. The model is to be used for the future numerical study of the engine. The volume flow rate results have been compared with the results obtained experimentally as presented in first part of this paper. The model has shown good agreement in terms of the flow rate at initial and final valve lifts but reduced by about 50% during half-lift region.